Sensory Properties and Antioxidant Activity of Siamese Orange (Citrus nobilis L.) Fruit Leather - Kunti Dewi Dhasi Aryawan; I Gede Arie Mahendra Putra; Cokorda Anom Bayu Sadyasmara; I Gusti Agung Bulan Mutiara Dewi; Putu Cempaka Sekarhita (Warmadewa University Press, 2024)
Siamese orange (Citrus nobilis L.) was a type of fruit widely cultivated and produced in Bali, but its utilization was not optimal. Siamese oranges were usually used for religious ceremonies, and if excess, they would lead to waste. Siamese oranges contain vitamin C, phenols, flavonoids, and limonene as antioxidants. In addition, peel contains 30% pectin. The combination of Siamese orange fruit and peels into fruit leather with the Zero waste concept (utilizing all parts of the Siamese fruit has great potential as a functional food product). Functional food is a product that is not only filled with nutrients but also has health benefits. Fruit leather is a processed product from fruit skin that has plastic characteristics obtained from pectin content of ingredients. This study aimed to determine the right concentration of fruit peel puree addition to produce siamese fruit leather with the best characteristics and its potential as a functional food. Randomized Block Design (RGD) was used with six treatment levels in addition to siamese peel puree concentration (0%; 5%; 10%; 15%; 20%; dan 25%), repeated three times to obtain 18 experimental units. Observed variables included Vitamin C by UV-Vis spectrophotometry, antioxidant activity by DPPH, and moisture content by gravimetric and sensory characteristics on hedonic test of colour, taste, aroma, texture, and overall acceptance. Data obtained were analyzed using analysis of variance, followed by Tukey test. According to raw materials, the assumption of Siamese fruit leather with the right concentration of Siamese peel puree has potential as a functional food.